Representation of the female members of YPJ in british media - Moreira Mineiro Drummond, Ana Luiza; Siqueira Batista, Maria Luiza; Mendes, Cristiano Garcia (Tensões Mundiais, 2021)
This paper aims to identify how the YPJ fighters have been framed in British media and to what extent these portrayals reflect misconceptions not only related to their gender, but also to a westernized judgment of their choices. In order to accomplish this, a qualitative analysis was employed based on a compilation of articles released by the BBC and The Guardian between 2014 and 2018.